Derivation of individualised item interrelatedness indices of careless responding - Gert K. Huysamen (SA Journal of Industrial Psychology, 2023)
Orientation: Presently, carelessly responding (CR) individuals are omitted in terms of several individual indices, including consistency-type indices (that compare performance on only a limited number of matched item pairs), and subsequently, the effectiveness of such screening is evaluated in terms of, among others, the group mean item interrelatedness (IIR) (based on all J[J – 1] item pairs).